Project-Based Learning: Improving Qiraah Skills In The Independent Learning Curriculum - Nadiya Robitatul Khasanah; Anyes Latifatul Insania (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The purpose of this study was to explore and analyze the impact of implementing the Project Based Learning (PBL) model in improving students' critical and analytical reading skills at Madrasah Tsanawiyyah Negeri 5 Banyuwangi. This study uses a qualitative approach with a case study at MTsN 5 Banyuwangi, using a purposive sampling technique. Data were collected through structured interviews, observations, and documentation. Data analysis follows the Miles and Huberman model, namely data reduction, data presentation, and drawing conclusions. The results are expected to contribute to the development of theories regarding strategies for creating an Arabic language environment in schools. The results of this study indicate that the Implementation of Project-Based Learning (PBL) at Madrasah Tsanawiyyah Negeri 5 Banyuwangi has a positive impact on critical and analytical reading skills, as well as mastery of qiraah material according to the Merdeka Belajar Curriculum. PBL encourages students to not only understand theory, but also apply knowledge in practical projects involving complex text analysis. The use of technology enriches students' literacy, increases reading interest, and supports active learning according to the Constructivism and Multiliteracies theories. Overall, PBL accelerates material mastery and builds student competencies holistically.